AB0608 Greater Organ Involvement and Disease Activity in Childhood-Onset than Adult-Onset With SLE (DATA from Reuma.Pt/Les). (9th June 2015) - Sousa, S.I.; Gonçalves, M.J.; Inês, L.; Eugénio, G.; Jesus, D.; Fernandes, S.; Terroso, G.; Romão, V.; Cerqueira, M.; Raposo, A.; Couto, M.; Nero, P.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multi-organ immune-mediated disease that affects predominantly women at reproductive age but may present itself at any age. Age at disease onset has a strong modulating effect on clinical presentation and course of disease. Although young patients may have a more aggressive disease, controversies persist regarding the impact of age at disease onset on SLE outcome. Objectives: Characterize childhood-onset, adult-onset and late-onset SLE and assess whether disease outcome differs in these three patient groups. Methods: Patients with childhood-onset (diagnosis ≤18 years) SLE fulfilling ACR 1997 criteria were identified in the Portuguese registry Reuma.pt/SLE and compared with adult-onset (≥19y and ≤49 years) and late-onset (≥50 years) SLE patients paired for disease duration. Results: Two hundred and sixty seven SLE patients with mean disease duration of 11.9±9.3 years were analyzed (Table 1 ). The number of fulfilled ACR criteria was significantly higher in childhood-onset SLE. A greater proportion of women, higher prevalence of arthritis and anti-SSA antibodies were noted in the adult-onset group. Hypertension, diabetes and thyroid disease were significantly more prevalent in late-onset SLE. Disease activity at last visit evaluated using the SLEDAI-2K was significantly higher in childhood-onset group than in the late-onset counterparts. SLICC/ACR damage index was numerically higher in late-onset SLE and significantly more patients in this group had irreversible damage. Cyclophosphamide and mycophenolate mophetil were used more frequently in childhood-onset SLE patients. Conclusions: The skin, kidney and neurological involvement are most common in childhood-onset, as well as the use of immunosuppressants, supporting the concept of a more severe disease. In contrast, patients with late-onset SLE have more comorbidities and irreversible damage. The age of SLE onset has a significant impact not only on the clinical characteristics and disease activity, but is also important for disease outcome. Disclosure of Interest: None declared